Maternal Acculturation - Moshtagh R. Farokhi DDS, MPH; Stephanie M. Cano PhD; Irene G. Bober-Moken DMD, MPH; Joseph A. Bartoloni DMD, MPH; Sue E. D. Cunningham PhD, RD, LD, CDE; Martha X. Baez RDH, MPH (SAGE Publishing, 2011)
A mother's cultural beliefs can affect her infant's health, but the influence of acculturation of Mexican-American women on their young children's oral health is unknown. The authors hypothesized that maternal acculturation impacts very young children's oral health practices favoring, in particular, the mothers who are more Anglo-oriented. A convenience sample of 204 predominantly Mexican-American women attending the Women, Infants, and Children Clinic in San Antonio, Texas, completed the Knowledge, Attitudes, Beliefs, Social Support, and Self-Efficacy of Oral Health (KASE-OH) and Acculturation Questionnaires. Results indicated that mothers with strong Anglo orientation were more likely educated in the United States, first visited a dentist while in elementary school, and breast-fed their children. Children belonging to Anglo-oriented Mexican-American mothers had stronger oral health practices, were more likely to breast-feed, were exposed to more sugary and acidic drinks, consumed higher levels of candy, had Medicaid coverage, and had stronger supervisions of tooth brushing practices.